Modelo teórico das técnicas de lente térmica e espelho térmico com acoplamento térmico Amostra-Fluido - Lukasievicz, Gustavo Vinicius Bassi (2011)
This work presents a theoretical study to take the heat transfer within the heated sample and out to the surroundings medium into account in the time resolved thermal lens and thermal mirror experiments. We solve the diffusion equations with heat flux boundary condition to obtain a semi-analytical solution for the temperature in the sample and in the surrounding fluid. In the low optical absorption case, the semi-analytical solution is used to model the thermal lens effects and the results are compared with the finite element analysis (FEA) software solution. Finite element analysis software provides numerical solutions to the heat transfer equations with realistic boundary conditions imposed by the experimental geometry. The FEA modeling results were found to be in excellent agreement with our solutions. The heat transferred to the air coupling fluid does not introduce any important effect in the sample phase shift when compared to the solution obtained without considering heat flux. The contribution from the thermal lens created in the air coupling fluid corresponds to approximately 2% of the sample's TL effect. When water is used as fluid the heat coupling leads to a more significant effect in both sample and fluid phase shift.